Integrated lateral correlation of tsunami deposits during the last 6000 years using multiple indicators at Koyadori, Sanriku Coast, northeast Japan. (15th March 2021) - Ishimura, Daisuke; Yamada, Keitaro
Abstract: Tsunami deposit studies have progressed and provided extensive information on the presence of tsunami deposits, their ages, and physical parameters especially after the devastating tsunamis from the 2004 Sumatra earthquake and 2011 Tohoku-oki earthquake. However, the abundance of such information makes it challenging to assess its uncertainty and reliability. These issues associated with the tsunami deposit studies are significant and should be resolved for the benefit of people using tsunami deposit data. In this study, we used multisite drilling cores to elucidate the sediment distribution in the study area. Additionally, we conducted micro-X-ray fluorescence core scanning, roundness analysis, and radiocarbon dating to obtain a certain identification of tsunami deposits and a reliable lateral correlation of sediments. Herein, we present a long-term tsunami history and tsunami deposit distribution at Koyadori on the Sanriku Coast in northeast Japan. Adding to tsunami deposits including the 2011 CE tsunami deposits reported in our previous studies, three tsunami deposits widely distributed in the Koyadori lowland were newly identified, concluding 14 tsunami deposits during the last 6000 years. This continuous and long record of large tsunamis in the central part of the Sanriku Coast provides an insight into the mechanisms of earthquakes and tsunamis occurring in the Japan Trench and is also expected to contribute to improvement in hazard assessment of earthquakes and tsunamis. Quantitative data (geochemical signature and gravel roundness) are also useful for a lateral correlation of tsunami deposits. In addition, the correlated sediment distribution enables the identification of an area with high preservation potential of tsunami deposits and estimation of paleoenvironment since 6 ka. Therefore, detailed information on tsunami deposits in one area is as necessary as revealing tsunami deposits across a wider area for future studies. Highlights: We identified 14 tsunami deposits widely distributed in Koyadori lowland over the last 6000 years. Geochemical signature and gravel roundness are useful for a lateral correlation of sediments. A lateral sediment correlation enables us to know preservation potential and paleoenvironment.